PENYULUHAN DAN PEMBUATAN SUPLEMEN MAKANAN DARI TANAMAN OBAT KELUARGA (TOGA) UNTUK MENURUNKAN STUNTING DI DESA SINDANG MEKAR WANARAJA - Mamay Mamay; Nurul Nurul; Titi Purwitasari; Raihan Nur Aulia (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Stunting is still a major problem in Garut Regency, especially Wanaraja District, Sindang Mekar Village. Tackling stunting requires a multi-sectoral approach that includes increasing access to nutritious food and offering better feeding practices. The use of family medicinal plants (TOGA) is one of the prevention efforts to overcome stunting, one of which is the manufacture of food supplements. The purpose of this service is to increase community knowledge and understanding regarding the use of family medicinal plants (TOGA) in treating stunting in toddlers, in addition to increasing community skills in using family medicinal plants to improve skin health. The stages of implementing community service start from preparation for supervision, implementation to evaluation. The service provided counseling and demonstrations on the manufacture of food supplements made from family medicinal plants such as turmeric, temulawak and lemon grass. After the community service activities were carried out, an increase in the knowledge and skills of families of stunted children in the use of family medicinal plants (TOGA) was obtained